OPERATIONAL RISK ANALYSIS FOR MANPOWER (DRIVER) ON POSTAL NETWORK - Maniah Maniah; Erna Mulyati; Dini Hamidin (STMIK Royal, 2023)
Abstract: PT. Indonesian logistics posts have cooperation in the postal network field, namely cooperation in sending goods or shipments at a certain time, a certain amount from one point to another in accordance with a warrant from the partner. Components of the postal network include Manpower, vehicles, postal operational control, and operational costs. This study aims to examine the problems and roots of problems that cause risk potential for the risk of postal network components, especially in the manpower component (driver), and know how high the impact of the risk. The research method used in this study is qualitative and semi-quantitative methods by conducting case studies. Data collection was carried out by interview/FGD, and the distribution of questionnaires. The results showed that the risk of manpower is at high and very high levels. The results of the study will provide recommendations to the manpower component (driver) in the form of risk mitigation and can be used by companies in managing operational risk on postal networks, especially in the manpower component (driver). Keywords: manpower; operational risk; postal network; risk mitigation. Abstrak: PT. Pos Logistik Indonesia memiliki kerjasama dalam bidang Jaringan Postal, yaitu kerjasama dalam mengirimkan barang atau kiriman pada waktu tertentu, jumlah tertentu dari satu titik ke titik lain sesuai dengan surat perintah dari mitra. Komponen pada jaringan Postal meliputi: Man Power, Kendaraan, Pengendalian Operasional Postal, dan Biaya Operasional. Penelitian ini bertujuan untuk mengkaji permasalahan dan akar masalah yang menimbulkan potensi kejadian risiko pada komponen Jaringan Postal khususnya pada komponen manpower (driver) dan mengetahui seberapa tinggi dampak risikonya. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dan semi kuantitatif dengan melakukan studi kasus. Pengumpulan data dilakukan dengan cara wawancara/FGD, dan penyebaran kuesioner. Hasil penelitian menunjukan bahwa risiko pada manpower berada pada level high dan very high. Hasil penelitian akan memberikan rekomendasi terhadap komponen manpower (driver) berupa mitigasi risiko dan dapat digunakan perusahaan dalam pengelolaan risiko operasional pada jaringan Postal khususnya pada komponen manpower (driver). Kata kunci: jaringan postal; manpower; mitigasi risiko; risiko operasional.